Development of accounting information as dataware basis for management of transport services - O.V. Oliinyk; I.V. Klymenko (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The package of internal management reporting in the context of specific business processes and cost elements was worked out in this study. The package includes the reporting forms about the formation and use of the vehicle fleet of a motor business, the report on the status of settlements with financial and operational leasing, the report on the status of the business process «Loading operations», the report on the material costs of the business processes «Shipping» and «Provision with fuel and oil materials», the report on the costs of labor and social measures (Single Contribution) of business processes «Shipping» and «Providing with fuel and oil materials», the report on the operating costs of business processes «Shipping» and «Provision with fuel and oil materials», and the report on the business process «maintenance». The authors worked out the procedure for the formation of the indicators developed on the base of organizational and methodological regulations of accounting transport services of the calculation system of their costs within each report.